Democratic Public Service (Case of License Operating Billboards in Makassar City) - Nani Harlinda Nurdin; Zulkarnain Hamson; Muhammad Nasir Mahmud; Nining Haslinda Zainal (Program Pascasarjana Universitas Negeri Makassar, 2023)
One of the points of concern in public administration is the organising of democratic public services. Democratic public service is the basic essence in realizing justice and social welfare. This can be realized if it involves all state stakeholders and domains in the administration of the government. In this perspective, public services should obtain genuine attention, be processed professionally and properly provided to residents of service users. Billboard licence is one of the types of licensing services issued by the government along with the rapid growth of companies or industries that have an impact on the increase in regional revenue. In addition to increasing regional revenue, the increase in billboards is directly proportional to various violations that occur because of services provided so that they are important to be handled. The purpose of this study is to evaluate the degree to which the Regional Revenue Agency of Makassar City, one of the government organisers in public services, organises democratic public services, particularly in the execution of billboards. The study employs a qualitative method and includes both primary and secondary data. Through in-depth interviews and observation, primary data is gathered. secondary information obtained from documents. Data reduction is then used to process the acquired data. The results of the study show that democratic public services have not been implemented. Complexity, bureaucracy, apparatus performance and community attitudes towards public services are factors that influence service integrity.